2017
DOI: 10.1152/ajpregu.00545.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reduced NHE3 activity results in congenital diarrhea and can predispose to inflammatory bowel disease

Abstract: TO THE EDITORS: With great interest we read the review just published in the American Journal of Physiology-Regulatory, Integrative and Comparative Physiology on "Novel developments in differentiating the role of renal and intestinal sodium hydrogen exchanger 3" by Dominguez Rieg and colleagues (2). The authors review recent studies that address the impact of NHE3 loss of function on renal and intestinal pathophysiology.Coupled operation of Na ϩ /H ϩ exchanger 3 (NHE3 encoded by the SLC9A3 gene) and Cl Ϫ /HCO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“… 47 , 48 A positive correlation between reduced NHE3 expression and increased severity of colitis has been demonstrated in rodent models of colitis. 49 , 50 Because LPA 5 regulates NHE3, it is possible that Lpar5 loss reduces NHE3 expression or function that may have increased diarrhea in DSS-treated Lpar5 ΔIEC mice. A recent study of NHE3 regulation in Lpar5 ΔIEC mice showed that basal NHE3 mRNA expression was decreased in Lpar 5 -deficient IECs, although no significant change in NHE3 activity was observed.…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 A positive correlation between reduced NHE3 expression and increased severity of colitis has been demonstrated in rodent models of colitis. 49 , 50 Because LPA 5 regulates NHE3, it is possible that Lpar5 loss reduces NHE3 expression or function that may have increased diarrhea in DSS-treated Lpar5 ΔIEC mice. A recent study of NHE3 regulation in Lpar5 ΔIEC mice showed that basal NHE3 mRNA expression was decreased in Lpar 5 -deficient IECs, although no significant change in NHE3 activity was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in NHE3 cause congenital sodium diarrhea, and inhibition of NHE3 has been reported in both enterotoxigenic and inflammatory diarrhea (1,11,14,31). In addition, reduced NHE3 activity can predispose humans and animals to inflammatory bowel disease (13,18).…”
Section: Introductionmentioning
confidence: 99%